2008
DOI: 10.1021/bi800278n
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution and Substrate Specificity of a Lantibiotic Protease

Abstract: Lacticin 481 is a lanthionine-containing bacteriocin (lantibiotic) produced by Lactococcus lactis subsp. lactis. The final steps of lacticin 481 biosynthesis are proteolytic removal of an N-terminal leader sequence from the prepeptide LctA and export of the mature lantibiotic. Both proteolysis and secretion are performed by the dedicated ATP-binding cassette (ABC) transporter LctT. LctT belongs to the family of AMS (ABC transporter maturation and secretion) proteins whose prepeptide substrates share a conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
77
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 50 publications
3
77
1
Order By: Relevance
“…Analysis of the leader peptide of CerA revealed two processing sites, including a GA cleavage site and an additional hexapeptide SDVQPE that were both conserved in ␤ subunits of the two-component lantibiotics cytolysin and lichenicidin (44,45). The putative CerT contained an N-terminal C39 cysteine protease domain, as did LctT and BovT, whose N-terminal 150-aa peptidase domain had been successfully reconstituted in vitro to recognize the double glycine motif (GA/GG) (46,47). Thus, maturation of cerecidins might undergo a two-step process involving complementary function of CerT and CerP.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the leader peptide of CerA revealed two processing sites, including a GA cleavage site and an additional hexapeptide SDVQPE that were both conserved in ␤ subunits of the two-component lantibiotics cytolysin and lichenicidin (44,45). The putative CerT contained an N-terminal C39 cysteine protease domain, as did LctT and BovT, whose N-terminal 150-aa peptidase domain had been successfully reconstituted in vitro to recognize the double glycine motif (GA/GG) (46,47). Thus, maturation of cerecidins might undergo a two-step process involving complementary function of CerT and CerP.…”
Section: Discussionmentioning
confidence: 99%
“…LanT (30,31). However, these studies are challenged by the failure to distinguish between which of the proposed leader peptide functions are affected by the changes in amino acid residues.…”
mentioning
confidence: 99%
“…The purified PEP of LctT can cleave off the leader peptide of both the modified and unmodified precursor peptide (9). On the other hand, we previously reported that full-length NukT can only digest modified NukA (15).…”
Section: Discussionmentioning
confidence: 97%
“…Members of this ABC transporter subfamily are involved in the secretion of proteinaceous compounds and contain an additional N-terminal domain involved in the processing of their substrates at the so-called double glycine site at the C terminus of the leader peptide (7)(8)(9). There are only a few studies on the N-terminal peptidase domain (PEP) of AMS proteins.…”
mentioning
confidence: 99%